2013
DOI: 10.1016/j.str.2013.08.020
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis for Eliciting a Cytotoxic Effect in HER2-Overexpressing Cancer Cells via Binding to the Extracellular Domain of HER2

Abstract: Human epidermal growth factor receptor-2 (HER2) is a receptor tyrosine kinase directly linked to the growth of malignancies from various origins and a validated target for monoclonal antibodies and kinase inhibitors. Utilizing a new approach with designed ankyrin repeat proteins (DARPins) as alternative binders, we show that binding of two DARPins connected by a short linker, one targeting extracellular subdomain I and the other subdomain IV, causes much stronger cytotoxic effects on the HER2-addicted breast c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
132
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(142 citation statements)
references
References 60 publications
8
132
0
2
Order By: Relevance
“…However, our SPR data suggests that peptide 1 as well as its conjugates 4 and 7 bind to EGFR domain 1 in the absence of ligand EGF, indicating that the conjugates also bind to EGFR in closed conformation. Such models have been proposed in the literature for binding of bi-specific affibody ligands that target EGFR and HER2 dimers [46], as well as HER2 dimers in open and closed conformations [47]. Hence, our SPR and modeling studies suggest that conjugates 4 and 7 can bind to monomer EGFR, as well as dimer EGFR, in open or closed conformations.…”
Section: Resultsmentioning
confidence: 61%
“…However, our SPR data suggests that peptide 1 as well as its conjugates 4 and 7 bind to EGFR domain 1 in the absence of ligand EGF, indicating that the conjugates also bind to EGFR in closed conformation. Such models have been proposed in the literature for binding of bi-specific affibody ligands that target EGFR and HER2 dimers [46], as well as HER2 dimers in open and closed conformations [47]. Hence, our SPR and modeling studies suggest that conjugates 4 and 7 can bind to monomer EGFR, as well as dimer EGFR, in open or closed conformations.…”
Section: Resultsmentioning
confidence: 61%
“…Other multivalent antibody-based or designed ankyrin repeat proteins (DARPins) that target HER2 or HER3 have been recently described 53 - 55 . Specifically, a tetravalent antibody (MM-141), with a similar design to TAb6 in the current study, that targets both HER3 and IGF-1R has been shown to have anti-proliferative effects both in vitro and in vivo 54 .…”
Section: Discussionmentioning
confidence: 84%
“…This feature may allow new fusion formats that target two distinct ERBB2-epitopes to be constructed. A similar strategy using designed ankyrin repeat proteins targeted to different epitopes on ERBB2 has shown a high potential for cancer treatment in vitro that did not rely on the addition of functional payloads [31]. Furthermore, binding assays on ERBB2-positive human cancer cells demonstrated that the ADAPTs specifically recognized the native receptor (Figure 4C).…”
Section: Discussionmentioning
confidence: 97%